Exploration and Practice of Cloud Platform About Supporting Telecom Operators Intensive Management - Jingwei Yang; Lin Hu; Jinling Li; Zhiyong Liu (Dianxin kexue)
One solution was presented that telecom operators can achieve whole network resource intensive management by building centralized and unified cloud platform.Some problems were analyzed in detail and further resolved when bringing into and managing resource.The unified management,unified dispatch and unified presentation of resource by decentralization of authority and domain can be achieved,automatic opening of service by means of process connection can be achieved.The usage and use efficiency of monitored resource were also discussed combined with the actual application in cloud computer platform,which can provide evidence for intensive usage of resource.